pH-independent uptake of hepatitis B virus in primary human hepatocytes - Hagelstein, Jens; Fathinejad, Farideh; Stremmel, Wolfgang; Galle, Peter R. (Virology, 1997)
The replication cycle of the hepatitis B virus (HBV) is still incompletely understood. In particular, the early steps of the viral life cycle, such as absorption, penetration, uncoating, and nuclear translocation require further clarification. In this study we performed infection experiments with HBV in primary human hepatocyte cultures. To further elucidate the possible mechanism of virus uptake, infection experiments were performed at different pH levels, after pretreatment of viral particles with acidic buffers and in the presence of lysosomotropic agents (chloroquine and ammonium chloride, respectively). Using a selective PCR technique which discriminates between input virus DNA and the earliest replicative form, we could demonstrate viral replication 36 hr after inoculation. HBV was taken up most efficiently at a pH of 7.4. Infection was still successful after pretreatment of viral particles at low pH and was unaffected by the presence of lysosomotropic agents. In conclusion, this suggests HBV to be a pH-independent virus.